Standard ideals in weighted algebras of Korenblyum and Wiener types - Galé, José E.; Wawrzynczyk, Antoni (MATHEMATICA SCANDINAVICA, 2011)
We introduce two types of Banach algebras of analytic functions on the unit disc which can be seen as weighted versions of closed primary ideals of the Korenblyum and (analytic) Wiener algebras, respectively. Such types of algebras arise in connection with convolution Banach algebras of Sobolev type, on the positive half-line, and their discrete analogues defined in terms of higher order differences. We show that all closed ideals are standard for algebras in the first class, and that closed ideals with countable hull are standard in algebras of the second class.